PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE PICTURE AND PICTURE TERHADAP HASIL BELAJAR - Melya Sari; Sumadi Sumadi; Edy Haryono (JPG (Jurnal Penelitian Geografi), 2016)
This research was aimed at finding out (1) the difference between the students achievement that used cooperative learning model of picture and picture type and the students achievement at twelfth grade of social 2 that used conventional learning model, (2) the effect of activities in using cooperative learning model of picture and picture type on the students learning achievement. Quasi experiment was used in this study. The populations were the students at twelfth grade of Social 1 and 2. To analyze the data, T-Test and linear regression analysis were used. The results showed that (1) there was a difference between the students achievement that used cooperative learning model of picture and picture type and the students achievement that used conventional learning model, (2) there was an effect of activities in using cooperative learning model of picture and picture type on the students learning achievementPenelitian ini bertujuan untuk mengetahui (1) perbedaan hasil belajar siswa yang menggunakan model pembelajaran kooperatif tipe Picture and Picture dengan hasil belajar siswa yang menggunakan model pembelajaran konvensional, (2) pengaruh aktivitas penggunaan model pembelajaran kooperatif tipe Picture and Picture terhadap hasil belajar siswa. Penelitian menggunakan metode quasi eksperimen. Populasi dalam penelitian ini adalah siswa kelas XII IPS 1 dan kelas XII IPS 2. Teknik analisis data yang digunakan adalah uji t dan analisis regresi linier sederhana. Hasil penelitian menunjukkan bahwa (1) ada perbedaan hasil belajar siswa yang menggunakan model pembelajaran kooperatif tipe Picture and Picture dengan hasil belajar siswa kelas yang menggunakan model pembelajaran konvensional, (2) ada pengaruh aktivitas penggunaan model pembelajaran kooperatif tipe Picture and Picture terhadap hasil belajar.Kata kunci: pembelajaran kooperatif , model picture and picture, hasil belajar geografi